Pandemic borders and expenditure impact: Intervention and forecasting insights from Australia - Mitchell Lewis Horrocks; Adrian Gepp; James Todd; Bruce James Vanstone (Annals of Tourism Research Empirical Insights, 2025)
The coronavirus pandemic had a devastating effect on tourism. This paper develops an integrated intervention analysis and forecasting methodology for crisis impact assessment to investigate the economic impacts of border restrictions for a popular tourist destination in Australia, the Gold Coast. Using anonymised and aggregated daily Visa expenditure data from 2018 to 2020, this paper investigates domestic and international visitors' responses to border restrictions and their subsequent easing. Responses are influenced by policy severity, proximity to destinations, and broader pandemic conditions, with international markets experiencing the greatest expenditure impact. Domestic intrastate visitors drove initial recovery, while interstate visitors faced barriers like non-reciprocal travel arrangements and frequently changing restrictions. Travel restrictions disproportionately affected tourist-oriented businesses and altered the spatial distribution of visitor spending.
Keywords: 330; Card transaction data; Coronavirus pandemic; Intervention analysis; Time series modelling; Tourism crisis; Tourist expenditure